Teachers’ Strategies in Developing Kalām (Speaking) Skills of Madrasah Aliyah Students: A Descriptive Qualitative Study - Rohanda Rohanda; Bintang Helmi Putra; Siti Latifah (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to provide an in-depth description and mapping of the various strategies used by teachers in Madrasah Aliyah (MA) to develop students’ kalām (speaking) skills, as well as to analyze the pedagogical considerations underlying the selection of these strategies. The research focuses not only on the types of strategies applied but also on the rationale, classroom needs, and instructional contexts that shape teachers’ practices in teaching speaking skills. A descriptive qualitative approach was chosen because it allows the researcher to capture the natural dynamics of classroom interaction and to understand the patterns, meanings, and considerations that emerge from teachers’ and students’ experiences. Data were collected through participatory classroom observations, in-depth interviews with teachers and students, and documentation studies involving lesson plans, teacher reflection notes, and students’ task results. All data were analyzed using the interactive model of Miles, Huberman, and Saldana, which includes iterative processes of data reduction, data display, and conclusion drawing. The findings indicate that teachers apply an eclectic set of strategies grouped into three main categories: (1) Lexical and psychological preparation, involving scaffolding, key vocabulary, and model dialogues; (2) Guided practice, including pair work, simple role-plays, and structured question–answer activities; and (3) Affective–corrective strategies, such as recasting, positive feedback, and delayed correction. The selection of these strategies is based on three primary considerations: addressing students’ psychological barriers (qalaq al-lughah), overcoming limited vocabulary that inhibits speaking fluency, and adapting to large class sizes and the lack of a supportive bī’ah lughawiyah (language environment), which requires teachers to adjust their strategies to the realities of the classroom.